Respuesta :
Answer:
The solution to this equation could not be determined.
Step-by-step explanation:
Simplifying
r + -5h = hr + 2h
Reorder the terms:
-5h + r = hr + 2h
Reorder the terms:
-5h + r = 2h + hr
Solving
-5h + r = 2h + hr
Solving for variable 'h'.
Move all terms containing h to the left, all other terms to the right.
Add '-2h' to each side of the equation.
-5h + -2h + r = 2h + -2h + hr
Combine like terms: -5h + -2h = -7h
-7h + r = 2h + -2h + hr
Combine like terms: 2h + -2h = 0
-7h + r = 0 + hr
-7h + r = hr
Add '-1hr' to each side of the equation.
-7h + -1hr + r = hr + -1hr
Combine like terms: hr + -1hr = 0
-7h + -1hr + r = 0
Add '-1r' to each side of the equation.
-7h + -1hr + r + -1r = 0 + -1r
Combine like terms: r + -1r = 0
-7h + -1hr + 0 = 0 + -1r
-7h + -1hr = 0 + -1r
Remove the zero:
-7h + -1hr = -1r
Combine like terms: -1r + r = 0
-7h + -1hr + r = 0
The solution to this equation could not be determined.
Answer:
- r = 7h/(1 - h)
Step-by-step explanation:
Given
- r - 5h = hr + 2h
Solving for r:
- r - 5h = hr + 2h
- r - hr = 5h + 2h
- r(1 - h) = 7h
- r = 7h/(1 - h)